Filogeografia Intraespecífica de Lonchorhina aurita (Chiroptera, Phyllostomidae) - Azevedo, Mariana Silva (2013)
The bat species Lonchorhina aurita (Chiroptera:Phyllostomidae) has a wide geographic distribution, occurring from the South Mexico to East of Brazil. Previous studies exposed some evidences of genetic structure among populations from North and South Atlantic Forest (AF), based on a short sample size of a few different localities and a controversial taxonomic history. Thus, herein we aimed to identify the phylogeographic and demographic patterns in L. aurita using a broader sample size in a larger geographic scale. For this purpose we used three molecular markers: two from the mitochondrial DNA (cytochrome b, cytb, and the hypervariable region I of the mitochondrial control region, HVI) and one nuclear marker (Recombination Activator Protein 2, RAG2). Thus, we build the phylogenetic relationship among the DNA sequences, calculated the polymorphisms values to the populations and estimated the population index to infer the demographical trends. We found 19 haplotypes to the cytb gene and 12 haplotypes to the HVI region. To the nuclear gene RAG2, we found only two haplotypes, that showed a minor nucleotide difference and, therefore, no analysis were made with this molecular marker. Through the concatenated analysis of both mitochondrial markers, six clades were formed, each one corresponding to a different geographic locality. The clade I clustered specimens from north of AF and one from the Amazon forest in the Brazilian State of Pará. The clade II clustered specimens from the south of AF. The clade III grouped specimens from the Amapá state. Clade IV grouped individuals from Suriname, clade V was built by Equator and Peru specimens and, finally, the clade VI clustered individuals from Honduras and México. Both the intraspecific genetic distance (2,2%) and the genetic inside the clades (0 to 0.91%) were very small, while the genetic distance among the clades showed values between 1.9 to 3.4%. Based on the low genetic distance between samples of L. aurita e L. inusitata (2.3%), our results raises taxonomic questions about Lonchorhina species. The haplotype network indicated strong geographic structure, being higher to cytb than the HVI. The indexes of demographic history pointed to scenario of recent population growth in some populations, and the divergence time among the clades were estimated in, at least, 230 hundred years ago. The population analyses indicate a strong genetic structuration amongthe populations and groups of populations. Thus, we conclude that the L.aurita is highly structured in geographic clades, and that this pattern can be explained by historical elements, described by consecrated theories used in phylogeographic studies, and to behavior and ecological trends of this species.